Requirements For The Application Of Total Quality In The University Educational System In Light Of The Information And Technological Revolution - AL-Momani, Mohammad Omar; Alrabadi, Insaf George (Científic@ - Multidisciplinary Journal, 2023)
Background: We live today in a very complex and changing world. We are all at the center of the event, and no one can be isolated from this huge development in human knowledge. Knowledge flows like a waterfall, and change is rapid, and the invasion of cultures is dangerous, and informatics has swept away every belief that calls for backwardness that chained humanity. With its restrictions for centuries, education is no longer a service issue but a national security issue, and investment in people is linked to the development of the people’s productive, economic and military capabilities, and the issue has become the preparation and rehabilitation of capable youth armed with science, knowledge and technology. Purpose: This study aims to identify the requirements for the application of total quality in the university educational system in light of the information and technological revolution. Methods: The qualitative analytical descriptive approach was used, the limitations of which are limited to higher education institutions. Results: The study concluded the need for a feasible and effective educational system, centered on the student through his interaction and active participation, in which computer technologies and information and communication technology represented in local networks and the global Internet play a promising role based on the concept and philosophy of total quality in education. Conclusions: We conclude that the nature of modern business requires educational and academic institutions to prepare students with a different set of skills other than those adopted by the old education system; The shape of educational institutions will be very different from what it is now, and the shape of the classroom will differ so that there will be a computer for each student, and departments in faculties will be able to communicate with different libraries to get what they want from references, scientific materials or educational software, and the shape of the course will differ from the usual It is likely that it will be replaced by a floppy or optical disk, and there will be a new type of teacher and students.